Tambores para a rainha da floresta: a inserção da umbanda no Santo Daime - Alves Junior, Antonio Marques (2007)
The presence of the Umbanda inside Santo Daime, verified in the sum of precepts and rites that make up the Daimistic cosmovision, gained visibility from the eighties onward, in the epicenter of the expansion that led this religion to the outer limits of the Amazonian Forest. Under the command of Sebastião Mota de Melo, the Santo Daime witnessed the growth of Umbanda relevancy in its doctrinaire constellation, to the point of being distinguished by this Umbanda presence in the context of the Ayahuascan religions, among those the ones derived from the creation of Mestre Irineu. In the generation guided by Padrinho Sebastião, a handful of occurrences precipitated the scattered nonetheless present elements that allowed the reception of the Umbanda. The first one resulted from the impact of the arrival of a macumbeiro who bewitched the young Daimistic community and its spiritual leader with his performances so familiar to our niche: consultations, warnings, demands and theatricalism. One could see in these events a fight between the forces of Truth and the legions of evil, represented by the King of Exus, the Tranca Rua, that, in the end, under the light of the sacred beverage, signed a pact with the Santo Daime: he would be its guardian against these wicked spirits. The Umbandistic ethos was silently being hardcoded into the community imaginarium. The last years of the life of Padrinho Sebastião were concurrent with the growth of the Santo Daime, particularly in Rio de Janeiro city. Impregnated with the perspectives of the counterculture that seemed to link the mythical Forest and the exotic Umbanda, both traditions found themselves in the personas of his Padrinho and of a Mãe de Santo from Rio de Janeiro, leading a group of disciples that was arriving at Santo Daime. Some of those came to have a central role in the design of the rites that expressed this alliance. The role of the successor of Padrinho Sebastião, his son Alfredo Gregório de Melo, was to acknowledge the maybe irresistible demand of the Umbanda, and express it through the creation of new rituals formalizing, so to speak, that presence, and placing it closer to the center of its forest of faith